2023
DOI: 10.3389/fmed.2023.1107148
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient and physician global assessments of disease activity in anti-neutrophil cytoplasmic antibody-associated vasculitis

Abstract: ObjectiveTo compare physician and patient assessments of global disease activity in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and to identify associated factors.MethodsGlobal disease activity scores (0–10 points) were retrospectively analyzed from physicians and patients with AAV at each outpatient visit from 2010 to 2020. We compared the scores and performed a linear regression with a random effects to identify associated factors.ResultsPatients (n = 143, 1,291 pairs, 52% female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The high proportion of BD is caused by a special consultation for BD in one of the participating centres. The gender distribution shows, comparable to other European cohorts, the highest proportion of women in TAK [ 20 ], more women than men with GCA [ 21 ], more men than women with BD [ 22 ] and a relatively balanced ratio in AAV [ 19 , 23 25 ]. Considerable differences in the age of onset, ranging from 28 (BD) to 67 years (GCA), are indicated.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The high proportion of BD is caused by a special consultation for BD in one of the participating centres. The gender distribution shows, comparable to other European cohorts, the highest proportion of women in TAK [ 20 ], more women than men with GCA [ 21 ], more men than women with BD [ 22 ] and a relatively balanced ratio in AAV [ 19 , 23 25 ]. Considerable differences in the age of onset, ranging from 28 (BD) to 67 years (GCA), are indicated.…”
Section: Discussionsupporting
confidence: 53%
“…It can be assumed that the physician assessment is based on other parameters (laboratory parameters, organ involvement) than the patient assessment. A study by Rode et al confirms to this assumption showing a high association between physician-reported disease activity and increased CRP values as well as shorter disease duration in contrast to a high association between patient-reported disease activity and patient-reported limitations regarding pain, function and general well-being in patients with AAVs [ 23 ]. Hurtado-Arias et al found correlations between patient global assessment and social and emotional impact, physical function and concerns about the future in AAVs [ 36 ].…”
Section: Discussionmentioning
confidence: 92%